Pengaruh Metode Outdoor Study Berbasis Pembelajaran Demokratis dalam Meningkatkan Hasil Belajar Siswa SMP Pada Mata Pelajaran IPA - Zusje Wiesje Merry Warouw; Firnalia Arruan Boyong; Ni Wayan Suriani; Ester Caroline Wowor; Widya Anjelia Tumewu (Postgraduate, University of Mataram, 2023)
This research aims to determine the effect of the outdoor study method based on democratic learning in improving junior high students' learning outcomes in science subjects. The research method we used is a quasi-experimental research with a nonequivalent control group design. The population in this study were all seventh-grade students at SMP Negeri 6 Tondano, while the research sample consisted of students in classes VII A and VII B. We obtained the research sample via a random sampling technique. Data were obtained from the pre-test before being given treatment and the post-test after being given treatment. The results showed that the average post-test result for the experimental class was 74.53, while the control class was 58.00. The t-test on the difference in the experimental and control groups' post-test scores shows the results of tcount = 37.91 > ttable = 2.011 so that H0 is rejected and H1 is accepted. Thus, the outdoor study methods based on democratic learning improve students' science learning outcomes on the interaction between living things and their environment topic at SMP Negeri 6 Tondano